Penyesuaian Diri Pada Pasangan Perjodohan di Kampung Madura - Aini, Asri Khuril; Nuqul, Fathul Lubabin (UIR Press, 2019)
This study aims to determine the processes and problems in arranged marriages, the potential for violence experienced by couples and the pattern of solutions in overcoming the problems of paired couples. The research method used is a qualitative research method with a phenomenological approach. Data collection techniques are using interview techniques. The research used purposive that are chosen based on specific characteristics, namely a maximum age of one year of marriage and marriage to the matched system. This study involved three married couples who were married to the matchmaking system. The results of this study explain that the process of adjustment in an arranged marriage partner has different periods, from the data in the field of adjustment on the groom's shorter period is different from the period on the bride who needs a long time in adjustment. The adjustment process involved is not only on both sides but also the family, and the environment also contributes to the adjustment process. The couple adjusts to a way to stay in excellent communication, open, mutual respect, maintain the feelings of the couple, respect and discuss to solve the problems faced and finally the couple managed to adjust well.